Pengembangan Instrumen Tes Identifikasi Bakat Bolabasket Untuk Anak Usia Dini - Susanto, Nugroho; Wiriadinata, Windo; Rusdiawan, Afif (JOSSAE (Journal of Sport Science and Education), 2022)
This study aims to make a valid and accurate early childhood basketball skill test based on basketball skill indicators. The method used is a mix of qualitative, quantitative and Brog and Gall development methods with ten stages. The subjects in this study were elementary school students in the city of Padang. In this study, male and female elementary school students aged 6 to 10 years were selected using a purposive selection technique. With SPSS 21 program, data were analyzed using normality test and homogeneity test. The results obtained in the large-scale test of material experts are 85% sports measurement test lecturers, media experts who are tested by computer experts by 87% and licensed trainer practitioners test with 90% results. With results of more than 80% in three stages of the initial test, small-scale test and up to the large-scale test stage, it can be concluded that development research is a new product in the basketball sports measurement test for early childhood, based on these results, it is stated that this development test can be used with good test effectiveness and efficiency.